Metamorfoses: filme para uma narrativa coreografada - Marisa, Cláudia (2017)
Metamophosis is a film project, which will be presented as a case study that intends to explore the dialogue between dance, music and film in a collaborative/devising process. Our aim is to research the implications of film (and therefore its role) during an artistic process: from the writing of the script to endeavour the consequences in the performance practice (both the relation between the different art fields present here, and between these last and the method used). Many arguments about art assume that they are expressing the truth. However, and following Merleau-Ponty’s assertion that art does not provide us with access to the “Real”, but rather with a version of reality, one can note that artistic narratives move into fiction territories containing one or more implicit truths. Most narratives highlight neither the process of construction this “truth” nor the specific position from which this “truth” is being constructed. To do so would reveal the fact that this “truth” is a particular version authored by a particular person, and is thereby open to question and revision. One name given to these implicit truths is verisimilitude. The concept of verisimilitude needs to be embodied, that is recognized as a metaphor and paradigm. Thus the question is not whether film can/should be metaphorical, but what specific “metaphors” are performers to “live by”. Briefly, Metamorphosis is an artwork that considers the results achieved by the collaborative process, and envisages new possibilities in film, where both traditional choreographic forms and cinema strategies are mixed.